2021
DOI: 10.1186/s12889-021-11607-w
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban determinants of vitamin a deficiency among under 5 children in Bangladesh: Evidence from National Survey 2017–18

Abstract: Background Vitamin A supplementation reduces child morbidity, mortality, and blindness of people, especially in developing countries like Bangladesh. This study explores significant determinants of vitamin A deficiency among preschool children in rural and urban areas of Bangladesh. Methods The data set was extracted from a nationally representative survey based on a cross-sectional study, the BDHS-2017-18. The base survey was conducted using a two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Children aged greater than 9 months had a significant effect on the good consumption of vitamin A than children of age in months 6–8. This is similar to a study finding a study in Bangladesh [ 36 ]. This result is probably due to the numerous carrying attitudes of parents regarding what types of foods they usually have to feed their children in different age groups.…”
Section: Discussionsupporting
confidence: 92%
“…Children aged greater than 9 months had a significant effect on the good consumption of vitamin A than children of age in months 6–8. This is similar to a study finding a study in Bangladesh [ 36 ]. This result is probably due to the numerous carrying attitudes of parents regarding what types of foods they usually have to feed their children in different age groups.…”
Section: Discussionsupporting
confidence: 92%
“…The severity of most infectious diseases in males can be explained by the impact of sex hormones on the T-helper 1/T-helper 2 cytokines, therefore, the female counterparts have higher morbidity and mortality because of greater immunopathology and/or autoimmunity [ 55 ]. Vaccination with BCG can develop cross-protective immunity by inducing an improved innate immune response for trained immunity against different microorganisms other than Mycobacterium tuberculosis [ 56 ] and consumption of vitamin A and different vaccination reduce childhood illness [ 57 , 58 ], however, the life-saving vaccination coverage has been disrupted by COVID-19 in low-and middle-income countries [ 59 ]. Children from families who have no access to safe drinking water, modern sanitation facilities, and living room materials have a greater likelihood of suffering from the infectious disease since their mother acts as a bearer of different microorganisms that may be imported into their body [ 60 – 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of most infectious diseases in males can be explained by the impact of sex hormones on the T-helper 1/T-helper 2 cytokines, therefore, the female counterparts have higher morbidity and mortality because of greater immunopathology and/or autoimmunity [55]. Vaccination with BCG can develop cross-protective immunity by inducing an improved innate immune response for trained immunity against different microorganisms other than Mycobacterium tuberculosis [56] and consumption of vitamin A and different vaccination reduce childhood illness [57,58], however, the life-saving vaccination coverage has been disrupted by…”
Section: Plos Onementioning
confidence: 99%
“…According to BDHS2017-18 reports, the level of wasting decreased by about half of the previous years [13]. Several studies have found a link between childhood malnutrition and a variety of factors such as an individual's socioeconomic status, demographic features, environmental factors, household factors, parental attributes, childfeeding habits, child morbidity, vitamin intake and vaccination coverage, geographic location, and residency [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%